The Implementation od Teacherâs Teaching Preparation in Teaching English at Anak Saleh Kindergarten Malang - Dewanti, Asri Kusuma (Proceeding of International Conference on Teacher Training and Education, 2016)
This paper focuses on the implementation of teacherâs teaching preparation in teaching English at Anak Shaleh Kindergarten Malang. The observation revealed that the teacher has performed interactive classroom activities in accordance with a well orderly lesson plan although there were some minor problems faced by the teacher in the implementation process.